The Effect of Motivation and Entrepreneurship on Interest in Entrepreneurship (Case Study Food Traders in the Field Triangle Head) - Putri Novianti; Mhd. Dani Habra (PT Inovasi Pratama Internasional, 2022)
This study aims to determine the effect of motivation and entrepreneurial mentality on interest in entrepreneurship (a case study of street vendors in the Lubuk Pakam Triangle Field). This research method uses quantitative descriptive data. The sample of this research is 49 street vendors. The results of this study indicate that motivation and entrepreneurial mentality affect the interest in entrepreneurship (a case study of street vendors in the Lubuk Pakam Triangle Field). The data were processed using SPSS 25 and tested with validity, reliability, classical assumption, multiple regression, hypothesis testing and coefficient of determination tests. The results showed that motivation had a positive and significant effect on interest in entrepreneurship, entrepreneurial mentality had a positive and significant effect on interest in entrepreneurship, and simultaneously motivation and entrepreneurial mentality had a positive and significant effect on entrepreneurship interest of street vendors in the Lubuk Pakam Triangle Field).